Fairy ponies: the magic necklace - Davidson, Zanna; Bongini, Barbara (Usborne Publishing Ltd London, UK, 2013)
Puck, the fairy pony, and Holly are visiting the Pony Queen when a powerful magic necklace - which grants its wearer whatever they wish for - is stolen from her Summer Palace. Puck and Holly's search for the thief leads them into the underwater world of the river ponies, an enchanting place of coral houses, clear waters